The Benefits of Teacher Professional Development (TPD) Program Based on Partnership, Technology, and Ethnoscience Approach to Improving the TPACK of Science Teachers - Yohanes Freadyanus Kasi; Ari Widodo; Achmad Samsudin; Riandi Riandi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
This study aims to determine the benefits of the Teacher Professional Development (TPD) program based on the partnership, technology, and ethnoscience approach to improving the TPACK of science teachers. It was conducted for 3 months from September to November 2021. The subjects consisted of 28 science teachers in Nagekeo Regency spread over 6 districts. This study was conducted using 2 methods, online and offline. In the online method, teachers met via Zoom to analyze the concept of science in Nagekeo cultural activities, adjust the concept to basic competencies, and evaluate the results of learning implementation in the classroom. In the offline method, teachers met directly to, in group, design a culture-based science lesson plan, and 4 teachers mutually agreed to carry out direct learning in class using the designed lesson plan. The results of the pretest and posttest of science teacher knowledge on indicators in the TPACK components were analyzed. The results demonstrated a significant difference between the pretest and posttest results of the TPACK components. The pretest results showed an average value of 39.89 in the low category while the posttest results showed an average value of 88.24 in the high category. These results indicate that the TPD program based on the partnership, technology, and ethnoscience approach is useful in improving the TPACK of science teachers.